The Resurgence of Speaking Confidence: The Use of Google Home in Pesantren - Nourmawan, Riski Bagus; Prasetyarini, Aryati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to explore the application of Google Home in Islamic boarding schools by students to determine how it is used, particularly in improving confidence in speaking English. Given these conditions, the researchers also looked at the challenges and obstacles that arise in an environment with its own characteristics compared to regular schools in general. On the other hand, this study is expected to contribute to the modernization of Islamic boarding schools. Methodology: This study employs a mixed-method approach designed sequentially and explanatorily through online surveys and semi-structured interviews. Quantitative analysis was conducted by adapting the Self-Regulated Listening Scale (Yabukoshi, T., 2024), modified to include items relevant to the study, which involved 107 participants. Then, semi-structured interviews were conducted with four selected students to further explore the research findings.Results: Quantitative analysis revealed that most students showed an increase in psychological readiness to speak, felt more comfortable practicing with Google Home. Qualitative findings confirm this; students described how Google Home provides a judgment-free practice environment, which helps reduce anxiety and motivates independent learning initiatives such as repeating instructions, bravely using new vocabulary, and improving pronunciation. Applications/Originality/Value: This study implements Google Home technology in Islamic boarding schools, which are institutions with very strict rules and routines. The author fills this gap by creating space for students to build confidence in speaking English.